ETIKA KEGURUAN SEBAGAI JIHAD AL-NAFS: ANALISIS PSIKO-SPIRITUAL HADITS TARBAWI - Fahim, Ali Masdar; Mabrur, Ahmad Sirojul; Anwar, Agus Nuril; Abdurrahman, Abdurrahman (Kreatif: Jurnal Pemikiran Pendidikan Agama Islam, 2026)
This study examines teacher ethics in Islamic tradition through the lens of jihad al-nafs (struggle against ego) as a psycho-spiritual framework to address contemporary issues of teacher burnout and professional meaning crisis. The prevalence of chronic exhaustion among educators necessitates an ethical model that transcends administrative compliance and engages internal spiritual transformation. Using qualitative library research with tahlīlī (analytical) approach, this study analyzes seven primary prophetic hadith related to teaching, complemented by classical exegetical works and Islamic psychology literature. Content analysis reveals four psycho-spiritual dimensions of teacher ethics: internal (sincerity and intentional awareness), emotional (patience and anger management), relational (humility and adab toward students), and transcendental (teaching as worship). The findings demonstrate that teacher ethics in the hadith tradition represents a continuous mujahadah process involving the transformation of nafs from al-ammārah (ego-driven) through al-lawwāmah (self-critical) to al-muṭma'innah (spiritually tranquil). The study proposes an implementable model integrating spiritual formation into teacher training programs, pre-service curriculum, and mentoring systems. This model offers religious self-regulation framework that enhances teacher resilience and spiritual well-being, positioning professional ethics not merely as external norms but as an ongoing journey of inner purification relevant to modern educational challenges.